Efektivitas Metode Drill terhadap Peningkatan Teknik Dasar Renang Gaya Dada - Ricardo V. Latuheru (Pusat Pengembangan Olahraga Universitas Pahlawan, 2026)
Purpose of the study: This study aims to examine the effectiveness of the drill method in improving the basic technique of breaststroke swimming among beginner swimmers in Makassar. Materials and methods: The research method employed a pretest-posttest control group design with 40 participants aged 10-14 years who were divided into experimental group (n=20) and control group (n=20). The experimental group received drill method training for 12 sessions (3 times per week for 4 weeks), while the control group followed conventional swimming lessons. Data collection used a breaststroke technique rubric consisting of five indicators: body position, arm movement, leg movement, breathing, and coordination, assessed by two certified swimming coaches. Data were analyzed using paired sample t-test and independent sample t-test with significance level of p<0.05. Results: The results showed a significant increase in the experimental group (t=8.432; p=0.000) with an average increase of 27.4%, while the control group showed a smaller increase (t=3.512; p=0.002) with an average increase of 12.8%. The post-test difference between groups was also significant (t=3.891; p=0.000). Conclusions: These findings indicate that the drill method is more effective than conventional methods for improving breaststroke swimming technique. This research contributes to the development of evidence-based swimming training programs for beginners in the context of swimming education in Indonesia.